Strategi Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai Kantor Cabang Dinas Pendidikan Wilayah Malang: Kota Malang-Kota Batu - Deny Indah Ariyani; Suyeno; Langgeng Rahmatulllah Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In meeting the needs and everything that the community wants, it is not surprising that there are branches of the Education Office including in Malang and Batu. This is because in addition to a wide geography it is also to provide easy access for all groups. Of course, it is not easy if it is not accompanied by good performance from existing employees, therefore this study will discuss development strategies for employee performance at branch offices. Research methods use qualitative or field. The results obtained by the branch office of the education office in Malang are three, namely Batu, Malang City and Malang Regency. Strategies carried out to strengthen human resources employee performance include: understanding the vision and mission and tasks, good leadership roles, training and development through various activities, reward or intensive, monitoring and improvement